Pengaruh Resilience dan Emotional Intelligence Karyawan pada Masa Pandemi Covid-19: Work Engagement Sebagai Intervening - Aprilia, Linda; Faradis, Jauhar (UIN Sunan Kalijaga Yogyakarta, 2022)
Research Aims: This study aims to determine the effect of resilience and emotional intelligence during the pandemi Covid-19 at BPRS Bangun Drajat Warga Yoyakarta through work engagement as an intervening variable. Design/methodology/approach: The sampling technique used is purposive sampling. The population in this study were 38 employees of BPRS Bangun Drajat Warga Yogyakarta. The data collection methods used were questionnaires and interviews, and the data analysis tools used were multiple linear regression and path analysis using software IBM SPSS 25.0. Research Findings: The results of this study indicate that the resilience variable does not affect work engagement but does affect employee performance during the pandemi Covid-19, the emotional intelligence variable does affect work engagement but does not affect employee performance during the pandemi Covid-19, the work engagement variable affect employee performance during the pandemi Covid-19, and the work engagement variable was unable to mediate the effect of resilience on employee performance but was able to mediate the effect of emotional intelligence on employee performance during the pandemi Covid-19 at BPRS Bangun Drajat Warga Yogyakarta.